Tourism Policy In United Kingdom - Siti Rogaya Arvanda Shaputri; Bakhora Kuvondikova; Muhammad Arman Muhammad Nazry (Peerian Journals Publishing, 2024)
Tourism is exceptionally imperative for the UK's economy. It makes employment, brings cash, and makes a difference. Individuals learn approximately different societies. In 2018 and 2019, numerous sightseers went to the UK, making a difference in business like inns, food bloggers, and shops. During 2020 and 2021, the COVID-19 widespread caused huge issues for tourism in the whole country. Travel limitations and lockdowns halted numerous individuals from going in and going out. By 2022, tourism began to recoup. Occasions just like the Queen's Platinum Celebration made a different draw in guests once more. With this study, we examine tourism patterns within the UK from 2018 to 2022. It looks at the number of guests, their investing, and their travel choices based on their preferences. The study also investigates how government approaches, innovation, and supportability endeavors can offer assistance to make strides in tourism within the future.
Keywords: UK tourism; COVID-19; inbound tourism